Respostas
respondido por:
5
Explicação passo-a-passo:
No triângulo ABC, temos que
x + 2x + 16° + 2(3/4x + 10°) = 180°
3x + 16° + 2[(3x + 40°)/4] = 180°
3x + 16° + (3x + 40°)/2 = 180°
Multiplicando a equação acima por 2, vem que
6x + 32° + 3x + 40° = 360°
9x = 360° - 72°
9x = 288°
x = 288°/9
x = 32°
No triângulo BCM, temos que
y + x + 3x/4 + 10° = 180°
y + 32° + 3.32°/4 + 10° = 180°
y + 32° + 24° + 10° = 180°
y = 180° - 66°
y = 114°
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás